Analisis Posisi Kerja Tenaga Pengelasan dengan Pendekatan Ergonomi ANBM dan Reba untuk Meningkatkan Produktivitas: Studi Kasus pada Bengkel M.Star Purwosari Pasuruan - Muhammad Makin Salim; Muhammad Hermasnyah (MES Management Journal, 2025)
The development of the industrial world in Indonesia is experiencing rapid development. The development of this industry cannot be separated from the formal and informal sectors. One of the developments in the informal industry is the welding sector. Welding is a local connection between two or more metals using heat energy.M.Star Workshop is a motorbike repair shop in the Purwosari area, Pasuruan which provides manufacturing and welding services for motorbike frames. This workshop has 4 workers who work 8 - 10 hours a day every day. Based on the results of the interview, it was discovered that the operator experienced muscle complaints in several parts of his body. These complaints occurred in the back, neck, waist, knees, feet and hands during the welding and sanding process. This is because the body position when working requires workers to bend their bodies and fold their legs for hours. This research aims to analyze the ergonomic risks felt by workers when doing work and provide recommendations for improving work posture to increase work productivity. This research uses the Rapid Entire Body Assessment (REBA) method to assess work posture risks, the Nordic Body Map to determine workers' complaints, then uses Mannequin Pro Software to improve work posture. The results showed that worker 1 had a risk value of 7 and worker 2 had a risk value of 9. The Nordic Body Map score for worker 1 was 62 and worker 2 was 65. Improving work posture with Mannequin Pro Software reduced the risk value for worker 2 from 9 to 3 and reduces torque by 28% from 14 Nm to 10.